On weakly b-continuous functions in bitopological spaces - doi: 10.4025/actascitechnol.v35i3.15612 - Tripathy, Binod Chandra; Sarma, Diganta Jyoti (Acta Scientiarum. Technology, 2013)
In this article we introduce the notion of weakly b - continuous functions in bitopological spaces as a generalization of b - continuous functions. We prove several properties of these functions.